Beyond Infection: The Role of Stunting in Tuberculosis Susceptibility and Treatment Outcomes - Deddy Herman; Delmi Sulastri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Tuberculosis (TB) remains a major global health concern, particularly in developing countries. Stunting, a manifestation of chronic malnutrition, is prevalent in these regions and is increasingly recognized as a significant risk factor for TB. This systematic review aims to comprehensively analyze the impact of stunting on TB susceptibility and treatment outcomes. Methods: A systematic search of PubMed and ScienceDirect databases was conducted for studies published in the last 10 years, focusing on the relationship between stunting and TB. The PRISMA guidelines were followed for article selection and data extraction. Results: The review identified a significant association between stunting and increased TB risk. Stunted individuals exhibit impaired immune responses, making them more susceptible to TB infection. Moreover, stunting negatively affects TB treatment outcomes, including increased treatment duration, higher relapse rates, and greater mortality risk. Conclusion: Stunting is a critical determinant of TB susceptibility and treatment outcomes. Addressing stunting through comprehensive nutritional interventions is crucial not only for reducing the burden of malnutrition but also for enhancing TB prevention and control efforts.